Ubiquitination of BAM1 attenuates CLE peptide–mediated signaling in the root apical meristem - Yuanyuan Zhou; Fei Liu; Yongfeng Han; Jiaojiao Bai; Baowen Zhang; Wenqiang Tang; Xiaoping Gou; Yan Zhang; Dongping Lu (Proceedings of the National Academy of Sciences, 2026)
The plasma membrane-resident receptor-like kinases (RLKs) and their cognate peptide ligands play crucial roles in plant growth and development. The RLK BARELY ANY MERISTEM1 (BAM1) promotes phloem formation and regulates other aspects of root development. However, the mechanisms governing BAM1 protein degradation remain unclear. In this study, we demonstrate that two closely related ubiquitin ligases, RING DOMAIN LIGASE 1 (RGLG1) and RGLG2, specifically interact with BAM1 and its closest homolog BAM2. RGLG1/2 ubiquitinate BAM1/2 and mediate their degradation, thereby dampening BAM1/2 signaling. Treatment with the peptide CLE13 (CLV3/EMBRYO SURROUNDING REGION-RELATED 13) enhances the BAM1/2-RGLG2 interaction and the ubiquitin ligase activity of RGLG2, resulting in increased ubiquitination and degradation of BAM1/2 by RGLG1/2. The rglg1 rglg2 double mutant exhibits increased sensitivity to CLE13 compared to the wild type. Collectively, our findings demonstrate that RGLG1/2-mediated ubiquitination and degradation of BAM1/2 attenuate CLE13-mediated signaling in root meristem.